Developing explosive athletes: use of velocity based training in athletes - Mann, J. B. (Ultimate Athlete Concepts, 2016)
Bryan Mann, PhD has spent years in research, working with athletes and contemporary technology companies to explore velocity based training applications. This third edition of Developing Explosive Athletes has several improved and enhanced content features. In addition to all of the original information on the use and application of VBT, it includes insights into new technologies for velocity based training. It also explores some of the application based nuances which have been revealed since this book's first printing. In short, as the author puts it, velocity based training is a road map to more precise and effective training means